1990
DOI: 10.1128/jvi.64.7.3219-3225.1990
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for natural reassortants of human rotaviruses belonging to different genogroups

Abstract: Of 335 rotavirus isolates associated with diarrheal disease in Bangladesh that were culture adapted and subsequently characterized for electropherotype, subgroup, and serotype, 9 had properties that suggested they may be natural reassortants between human rotaviruses belonging to different "genogroups." Two of these were examined in greater detail by RNA-RNA hybridization with prototype strains representative of each of the three proposed human rotavirus genogroups. One subgroup II isolate, 248, with a "long" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
58
0
3

Year Published

1993
1993
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 46 publications
0
58
0
3
Order By: Relevance
“…Eighteen studies reported that none of the rotavirus specimens possessed an unusual combination of serotype and electropherotype. However, several studies reported strains having an unusual combination of serotype and electropherotype (4,6,16,55,57,64,72,74). The frequency of the isolation of these rotaviruses varied from nil (0/605 in New England) (7) to 2.7% (9/335 in Bangladesh) (72).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eighteen studies reported that none of the rotavirus specimens possessed an unusual combination of serotype and electropherotype. However, several studies reported strains having an unusual combination of serotype and electropherotype (4,6,16,55,57,64,72,74). The frequency of the isolation of these rotaviruses varied from nil (0/605 in New England) (7) to 2.7% (9/335 in Bangladesh) (72).…”
Section: Discussionmentioning
confidence: 99%
“…1) and G2. Serotype G2 strains possessing long RNA patterns have thus far been reported in six studies (1,6,31,43,65,72), and some were demonstrated by RNA-RNA hybridization to be reassortants between members of the Wa and DS-1 genogroups (35,72).…”
Section: Discussionmentioning
confidence: 99%
“…The experience of determining G types in Australia [Coulson et al, 1988;Unicomb et al, 19881, England [Noel et al, 19911, and Japan [Taniguchi et al, 19871 where most rotavirus G types are similar to the reference strains and types 1 and 2 are predominant, is different than i n Bangladesh where genetic reassortment of the viral genome occurs frequently [Ward et al, 1990;Ahmed et al, 19911 and the predominant G types change within a few months [Ward et al, 19911. Little is known about the distribution and seasonal variation of rotavirus G types in children in developing…”
Section: Discussionmentioning
confidence: 99%
“…So far, 14 G types and more than 20 P types have been differentiated indicating extensive genomic diversity within group A rotaviruses (Estes, 1996). As these proteins are coded for by different RNA segments and as rotaviruses reassort readily in doubly infected cells both in vitro (Garbarg-Chenon et al, 1984) and in vivo (Gombold and Ramig, 1986;Ward et al, 1990), the observed diversity due to various combinations of VP7 and VP4 types becomes very large.…”
Section: Rotavirusesmentioning
confidence: 99%